Social Class and Social Capital in China and Britain: A Comparative Study - Li, Yaojun (2013)
We use the China General Social Survey (2005) and the Home Office Citizenship Survey (2005) to study civic engagement and neighbourhood trust in China and Britain in this paper. We focus on class differences in participation in sports/recreation, religion, children's/adult education and public-welfare activities, and trust in the neighbours. We find higher levels of civic involvement in Britain but greater neighbourhood trust in China. This is mainly due to structural differences. China has a large proportion of peasants who have very low levels of civic involvement but very high levels of neighbourhood trust. Among the non-peasant population, the two countries have similar levels of class differences in civic (except religious) involvement. There are small class differences in China on neighbourhood trust, but marked effects in Britain. Overall, there is a greater similarity than difference in class effects in both civic engagement and social trust in the two countries. While differences in demographic attributes (and China's specific institutional arrangement, the household registration system, or hukou) account for some of the observed patterns, we also find more pronounced class than demographic effects in the two countries. Class plays a major role in the development of social capital.